Genome-wide identification, phylogeny and expression analysis of the SBP-box gene family in maize (Zea mays) - Wei ZHANG; Bei LI; Bin YU (Journal of Integrative Agriculture, 2016)
The SQUAMOSA promoter binding protein (SBP)-box genes encode a kind of plant-specific transcription factors (TFs) and play important roles in the regulation of plant development. In this study, a genome-wide characterization of this family was conducted in maize (Zea mays). Thirty-one SBP-box genes were identified to be distributed in nine chromosomes and 16 of them were complementary to the mature ZmmiR156 sequences. All the Z. mays SBP (ZmSBP) genes were classified into two clusters with eight subgroups according to the phylogenetic analysis of proteins, which were consistent with the pattern of exon-intron structures. The phylogenetic tree of the ZmSBP, Oryza sativa SBP-like (OsSPL) and Arabidopsis thaliana SBP-like (AtSPL) genes were constructed and all the SBP-box genes were divided into eight groups, which was the same as the classification of ZmSBP genes. The comparision of the expression profiles of all SBP-box genes in these three species indicated that most orthologous genes had similar expression patterns. The results from this study provided a basic understanding of the ZmSBP genes and might facilitate future researches for elucidating the SBP-box genes function in maize.